FGF2 Has Distinct Molecular Functions from GDNF in the Mouse Germline Niche - Kaito Masaki; Mizuki Sakai; Shunsuke Kuroki; Jun‐ichiro Jo; Kazuo Hoshina; Yuki Fujimori; Kenji Oka; Toshiyasu Amano; Takahiro Yamanaka; Makoto Tachibana; Yasuhiko Tabata; Tanri Shiozawa; et al. (2018)
Both glial cell line-derived neurotrophic factor (GDNF) and fibroblast growth factor 2 (FGF2) are bona fide self-renewal factors for spermatogonial stem cells, whereas retinoic acid (RA) induces spermatogonial differentiation. In this study, we investigated the functional differences between FGF2 and GDNF in the germline niche by providing these factors using a drug delivery system in vivo. Although both factors expanded the GFRA1+ subset of undifferentiated spermatogonia, the FGF2-expanded subset expressed RARG, which is indispensable for proper differentiation, 1.9-fold more frequently than the GDNF-expanded subset, demonstrating that FGF2 expands a differentiation-prone subset in the testis. Moreover, FGF2 acted on the germline niche to suppress RA metabolism and GDNF production, suggesting that FGF2 modifies germline niche functions to be more appropriate for spermatogonial differentiation. These results suggest that FGF2 contributes to induction of differentiation rather than maintenance of undifferentiated spermatogonia, indicating reconsideration of the role of FGF2 in the germline niche.